2007
DOI: 10.1039/b618579g
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of complexes formed by interaction of cationic gemini surfactants with deoxyribonucleic acid

Abstract: Cationic gemini surfactants, N,N-bis(dimethylalkyl)-alpha,omega-alkanediammonium dibromide [C(m)H(2m+1)(CH(3))(2)N(+)(CH(2))(s)N(+)(CH(3))(2)C(m)H(2m+1) x 2 Br(-), or m-s-m], have proven to be effective synthetic vectors for gene delivery (transfection). Complexes (lipoplexes) of gemini compounds, where m = 12, s = 3, 12 and m = 18 : 1(oleyl), s = 2, 3, 6, with DNA have been investigated using isothermal titration calorimetry (ITC), dynamic light scattering (DLS), zeta potential, atomic force microscopy (AFM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 45 publications
4
55
0
Order By: Relevance
“…Lipoplexes of gemini compounds, where m = 12, s = 3, 12 and m = 18 : 1 (Smisterova et al, 2001), s = 2, 3, 6, with DNA were investigated using isothermal titration calorimetry, dynamic light scattering (DLS), zeta potential, atomic force microscopy (AFM) and circular dichroism (CD) techniques. ITC data showed that the interaction between DNA and gemini surfactants is endothermic and the observed enthalpy vs. charge ratio profile depends upon the titration sequence (Wang et al, 2007a). Isoelectric points (IP) of lipoplex formation were estimated from the zeta potential measurements and show good agreement with the reaction endpoints (RP) obtained from ITC.…”
Section: Unsubstituted Gemini Surfactantssupporting
confidence: 59%
See 1 more Smart Citation
“…Lipoplexes of gemini compounds, where m = 12, s = 3, 12 and m = 18 : 1 (Smisterova et al, 2001), s = 2, 3, 6, with DNA were investigated using isothermal titration calorimetry, dynamic light scattering (DLS), zeta potential, atomic force microscopy (AFM) and circular dichroism (CD) techniques. ITC data showed that the interaction between DNA and gemini surfactants is endothermic and the observed enthalpy vs. charge ratio profile depends upon the titration sequence (Wang et al, 2007a). Isoelectric points (IP) of lipoplex formation were estimated from the zeta potential measurements and show good agreement with the reaction endpoints (RP) obtained from ITC.…”
Section: Unsubstituted Gemini Surfactantssupporting
confidence: 59%
“…The interactions between unmodified gemini surfactants (12-3-12, 12-12-12, 18:1-2-18:1, 18:1-3-18:1, 18:1-6-18:1) (Wang et al, 2007a) and pyrenyl-modified gemini surfactants with DNA have been studied previously in this manner, which provides important information on the nature of the interaction(s) between surfactant micelles and DNA for conditions of excess positive charge; i.e., conditions similar to those typically used to prepare complexes for transfection studies. The same types of interactions observed between unsubstituted gemini surfactants and DNA (described above) will occur for the various substituted gemini surfactants studied in this investigation; however, since the various substitutions are made within the head group region of the surfactant, this should result in noticeable changes in the binding interactions(s) which is indeed the case as seen in Figure 6.…”
Section: Substituted Gemini Surfactant Systemsmentioning
confidence: 99%
“…Figure 11 presents typical TEM (A and B) and AFM (C and D) images obtained for lipoplexes at L/D = 1000. This figure depicts non aggregated liposomes with DNA coils coming out from their surfaces seemingly connecting them; a feature that is more easily observed in the zooms shown in panels B and D. Such a morphology, referred to as the ''beads on a string'' conformation, has been observed not only for DNA-vesicle systems but also for DNA-micellar aggregates (Ruozi et al, 2007;Wang et al, 2007). In general, this structural conformation, occurring at low lipid to DNA ratios, is believed to appear because of packing and bending constraints on the long DNA molecules (Dan, 1998).…”
Section: Surface Chargementioning
confidence: 85%
“…Titrating DNA into 18:1-2-18:1 and 18:1-3-18:1 were different from those for 18:1-6-18:1 ( Figure 4B and 4C, respectively). The initial enthalpy at low DNA concentration was 15kJ which increased monotonically to more than 20 kJ mol, then the enthalpy dropped rapidly to near zero and remains close to zero up to the highest DNA concentration studied [21].…”
Section: Interactions Between Dna and Cationic Surfactantsmentioning
confidence: 97%
“…They have shown significant potential for use in non-viral transfection vectors for the delivery of genes into cells. Our group [21] studied the interaction of DNA with a series of N,N-bis(dimethylalkyl)-α,ω-alkanediammonium dibromide gemini compounds that simulates membrane components in terms of carbon chain length and chemical character, 18:1-s-18:1, where s = 2, 3, and 6 as well as 12-s-12, where s= 3 and 12. 18:1 signifies an 18-carbon chain with one double bond [22].…”
Section: Isothermal Titration Calorimetry (Itc)mentioning
confidence: 99%